Kajian keratan rentas mengenai masalah perlakuan di kalangan remaja di Jerijeh, Belawai, Sarawak : faktor-faktor risiko dan persepsi ibubapa - Abg Mohd Affendi, b Abang Yusop; Adibah, Ali; Amelia Karen, Gau; Dayang Suhana, Abang Madzhi; Essazul Imran, Mat Aris; Joyce Ee Sze, Zing; Maini, Sabait; Sharifah Ashrina, Wan Ali; Vijayan, Manogram; Wong Siong, Teck (Universiti Malaysia Sarawak, (UNIMAS), 2000)
cross sectional study on the prevalence of behavioural problems, the risk factors and perception of parents towards adolescent aged 13 - 19 years old in Kampung Jerijeh was done from 4 September-20 October 2000 by Year 4 Medical Students of Faculty of Medicine and Health Sciences) UNIMAS. 108 parents and 78 teenage respondents were studied using universal sample technique. 24 respondent had to be excludeds, as they could not be found for interview after three trials. This study was done by questionnaire cum interview technique. Two different sets of questionnaire were used for the adolescent respondent and parent respondent. Results of the study shows that 24.9% of respondent have taken alcohol before, 2.6% had sniffed glue, 33.3% had smoked and 52.6% had disciplinary problems. This study shows a statistically significant association between age and attitude with disciplinary problems. There are no significant association between knowledge of respondents with disciplinary problem. There are also no significant association between knowledge and attitude of respondents with disciplinary problems, alcohol abuse, smoking and glue sniffing. More male adolescent respondents had behavioural problems compared to their female counterparts. Some factors for these behavioural problems were identified as boredom, curiosity to try something different and peer influence. The majority of the parent respondents were not aware of behavioural problems in their children. An intervention program with the theme of `Remaja Berwawasan Tunggak Negara' was held from 24 September -8 October 2000 with the objective to increase the attitude and to increase the knowledge of adolescents regarding behavioural problems.